ABORSI: ANTARA TEKS DAN REALITAS (Telaah Atas Problematika Aborsi Dalam Perspektif Islam Dan Realitas Sosial) - Abdul Wasik (Universitas Islam Malang, 2021)
The issue of abortion is still a serious problem in the social reality of people's lives, including in our country in Indonesia. As stated by the Indonesian Child Protection Commissioner (KPAI) for Health and Drug Use to provide on illegal abortion in the world or in Indonesia. In 2016 there were around 56 million abortion women, 2018 decreased to 42 million, while in Indonesia there were around 2 million abortion cases. In this paper systemically will be discussed various ethical foundations of Islam about human reproduction, then the search for the position of abortion-ethical law in various Islamic perspectives which in this case is more emphasized on the results of ijtihad four Imam Mazhab where in the context of Indonesia-ness more dominantly applied the opinions of Imam Shafi'i and MUI. The answer to this abortion case is that abortion is not only underestimated as merely halal and haram in its law but must be considered between the text and its social reality so that the Qur'an and Al-Hadith truly become guidelines for Rahmatan Lil 'Alamin for humans .